2011
DOI: 10.1088/0004-637x/732/2/62
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Silicate Grain Nucleation and Growth in Circumstellar Outflows

Abstract: Based on its abundance, high bond energy, and recent measurements of its vapor pressure SiO is a natural candidate for dust nucleation in circumstellar outflows around asymptotic giant branch stars. In this paper, we describe a model of the nucleation and growth of silicate dust in such outflows. The sensitivity of the model to varying choices of poorly constrained chemical parameters is explored, and the merits of using scaled rather than classical nucleation theory are briefly considered. An elaboration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…Donn & Nuth [12] were initially rather critical of CNT for these reasons, although very recently they have shown that the lack of chemical equilibrium is perhaps not such a serious problem [13]. These workers have also introduced a scaled version of CNT [11]. Cherchneff & Dwek [14] have also recently discussed the shortcomings of CNT in some detail.…”
Section: Introductionmentioning
confidence: 99%
“…Donn & Nuth [12] were initially rather critical of CNT for these reasons, although very recently they have shown that the lack of chemical equilibrium is perhaps not such a serious problem [13]. These workers have also introduced a scaled version of CNT [11]. Cherchneff & Dwek [14] have also recently discussed the shortcomings of CNT in some detail.…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion is based on the theoretical calculations done by Dominik et al (2016) and the laboratory studies of Krause & Blum (2004). The nucleation models by Paquette et al (2011) and the dynamical models by Fleischer (1994) suggest a narrow grain size distribution with a strong peak at small grain sizes in the inner wind region 14 . Further out in the wind, in the region beyond 400 mas, the relative motions of the dust particles will be governed by thermal (Brownian) motions caused by the random collisions with the gas molecules and turbulence caused by the relative difference in stopping time (captured in the Stokes number) for various dust particles.…”
Section: Scenario 2: Enforced Dynamics In An Isotropic Windmentioning
confidence: 95%
“…This equation bears the implicit assumption of no further grain growth when the dust particles travel through the wind. However, an interesting finding by Paquette et al (2011) is that silicate grain nucleation occurs over a wide range in stellar radius -from approximately sevento more than 20 stellar radii in their models. This additional nucleation would provide more grains to capture photons and accelerate dust (and hence gas) farther from the star.…”
Section: Scenario 2: Enforced Dynamics In An Isotropic Windmentioning
confidence: 99%
“…Among all the gas-phase species of refractory elements that could be involved in this process, SiO is one of the most abundant. For this reason, it has been often discussed whether cluster formation by this species is the starter reaction for the sequence of processes that ultimately leads to the condensation of silicate dust particles (Donn et al 1981;Nuth & Donn 1982, 1983Gail & Sedlmayr 1986, 1998aAli & Castleman 2005;Nuth & Ferguson 2006;Reber et al 2006;Paquette et al 2011;, although other possibilities have also been discussed recently (Goumans & Bromley 2012;Plane 2013;Bromley et al 2014;Gobrecht et al 2016). …”
Section: Introductionmentioning
confidence: 99%